Caloric deficit in students of health sciences in a university of Lambayeque, 2018 - Becerra-Rojas, Becerra-Rojas (2020)
Objetive: Compare the required calories and calories consumed in university students of the Faculty of Medicine of the Catholic University Santo Toribio de Mogrovejo, 2018. The Study. Descriptive, cross-sectional study. A 24-hour reminder was applied to evaluate the amount of kilocalories ingested by students, designed by the National strategy of the Ministry of Health. Findings. 212 students from the schools of Human Medicine, Dentistry, Psychology and Nursing were interviewed; 62.7% were female and 37.3% were male. The average age was: 18.7 years ± 1.55. Of the total students of the Faculty interviewed, in the School of Human Medicine it was found that 31.03% have an excess of calories and 41.37% deficit. In the School of Dentistry, it was found that 77.55% have a calorie deficit, and 10.2% excess. The total average deficit of kilocalories 703,615 Kcal. ± 4.39. Conclusions. The calories consumed by students on a daily basis, is deficient compared to the calories they need according to their daily energy requirement.